Macrophage ATP citrate lyase deficiency stabilizes atherosclerotic plaques - Baardman, Jeroen; Verberk, Sanne G. S.; van der Velden, Saskia; Gijbels, Marion J. J.; van Roomen, Cindy P. P. A.; Sluimer, Judith C.; Broos, Jelle Y.; Griffith, Guillermo R.; Prange, Koen H. M.; van Weeghel, Michel; Lakbir, Soufyan; Molenaar, Douwe; et al. (Nature communications, 2020)
Macrophages represent a major immune cell population in atherosclerotic plaques and play central role in the progression of this lipid-driven chronic inflammatory disease. Targeting immunometabolism is proposed as a strategy to revert aberrant macrophage activation to improve disease outcome. Here, we show ATP citrate lyase (Acly) to be activated in inflammatory macrophages and human atherosclerotic plaques. We demonstrate that myeloid Acly deficiency induces a stable plaque phenotype characterized by increased collagen deposition and fibrous cap thickness, along with a smaller necrotic core. In-depth functional, lipidomic, and transcriptional characterization indicate deregulated fatty acid and cholesterol biosynthesis and reduced liver X receptor activation within the macrophages in vitro. This results in macrophages that are more prone to undergo apoptosis, whilst maintaining their capacity to phagocytose apoptotic cells. Together, our results indicate that targeting macrophage metabolism improves atherosclerosis outcome and we reveal Acly as a promising therapeutic target to stabilize atherosclerotic plaques. Inhibition of the metabolic enzyme ATP-citrate lyase can attenuate atherosclerosis by preventing dyslipidemia and potentially also by reducing macrophage-mediated inflammation. Here, the authors show that specific targeting of ACLY in macrophages results in more stable atherosclerotic plaques.